2020
DOI: 10.1111/cod.13645
|View full text |Cite
|
Sign up to set email alerts
|

Food allergens in skincare products marketed for children

Abstract: Background The application of preparations containing food allergens can cause percutaneous sensitization and provocation. The prevalence of food allergens in children's cosmetics is unknown. Objectives To analyse the prevalence of food allergens in skincare products marketed for children and their association with marketing claims and product price. Methods We reviewed 276 skincare product ingredient labels for the presence of milk, eggs, wheat, soy, oats, tree nuts, peanuts, and sesame. Results More than one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, few reports have examined the extent to which food allergens and essential oils are present in moisturizing personal-care products to be left on children's skin. To our knowledge, only one report has examined food allergens in children's skin care products [11]. The authors stated that the most common food allergens in personal skin care products for children are almonds, wheat, soy, oats, and sesame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few reports have examined the extent to which food allergens and essential oils are present in moisturizing personal-care products to be left on children's skin. To our knowledge, only one report has examined food allergens in children's skin care products [11]. The authors stated that the most common food allergens in personal skin care products for children are almonds, wheat, soy, oats, and sesame.…”
Section: Discussionmentioning
confidence: 99%
“…Adomaite et al showed significantly more food allergens in personal care products for the skin when marketing terms emphasizing "natural and organic" were presented, that is, almonds and wheat were the most common allergens [11]. This may be because the impression that products labeled organic are safe as skin care products for children is widely accepted by caregivers and more likely to be chosen as a marketing term [14].…”
Section: Discussionmentioning
confidence: 99%
“…Skincare products containing food-derivative ingredients are widely available on the market [ 7 ]. 39.1% of the skincare products for children were shown to contain at least one food allergen [ 10 ]. Among the allergens analysed, the most common were almonds, wheat, soya, followed by oats and sesame seeds.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, even in the absence of consumption by children, food allergens are found in bedding and play areas 34 . Skincare products are other possible sources of food allergens, especially those labeled “natural” or “ecological” that may contain food‐derived proteins 36 . The use of such skincare products has been shown to be associated with an increased risk of FA, 37–39 and children with AD should avoid such type of products.…”
Section: Emollients To Prevent Food Sensitization and Allergy: Why Sh...mentioning
confidence: 99%